2011
DOI: 10.1136/jmg.2010.087379
|View full text |Cite
|
Sign up to set email alerts
|

Germline PALB2 mutation analysis in breast-pancreas cancer families

Abstract: Mutations within the PALB2 gene are rare events that do not account for a substantial proportion of cancer susceptibility in breast-pancreas cancer families. Routine screening of breast-pancreas cancer families for the presence of PALB2 mutations appears to be low yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 15 publications
3
19
0
1
Order By: Relevance
“…Our results are in line with the results of these previous reports in which no PALB2 mutations, 9,14 or low prevalence of PALB2 mutations, 2,4,[7][8]10 were found. It should be mentioned that the relatively small sample size could be a possible explanation for that no mutation carrier was identified in the current study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are in line with the results of these previous reports in which no PALB2 mutations, 9,14 or low prevalence of PALB2 mutations, 2,4,[7][8]10 were found. It should be mentioned that the relatively small sample size could be a possible explanation for that no mutation carrier was identified in the current study.…”
Section: Discussionsupporting
confidence: 93%
“…2 Mutations in this gene may be associated with familial clustering of PC and BC. [1][2][3][4][5][6][7][8][9][10] Previous studies have shown that PALB2-mutation-positive familial BC (FBC) patients were significantly more likely to have a relative with PC, 5 and that nearly all PALB2-mutation positive familial PC (FPC) families were affected by at least one BC case. 4 Given these findings and the fact that the prevalence of gene mutations varies between different populations, we aimed to determine the prevalence of PALB2 mutations in Dutch cohorts of non-BRCA1/2 FPC patients and of non-BRCA1/2 FBC patients with a personal or family history of PC.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, PALB2 germline mutations have been independently implicated in both breast cancer (BC) and PC susceptibility [12,13]. In patients with PALB2-associated PC, a concomitant personal or family history of BC has been repeatedly observed [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The frequencies of these cancers in the family histories of our cohort are described in Additional file 1: Table S5A and Additional file 1: Table S5B, respectively. Multiple studies have identified PALB2 mutations in familial pancreatic cancer probands, several of which were found to have family histories including cases of breast cancer [8,29-31]. It should be noted that these mutations occur at relatively low frequencies (0–4%), which depend on the population being studied [8,32].…”
Section: Resultsmentioning
confidence: 99%